Т.ҚАЙЫПБЕРГЕНОВТЫҢ «ҚАРАҚАЛПАҚНАМА» РОМАН-ЭССЕСИНДЕ ЖАНАПАЙЛАРДЫҢ СТИЛЛИК ҚОЛЛАНЫЛЫЎЫ - Шынназарова, С.; Мамбетова, Г. (FAN va JAMIYAT, 2020)
The article deals with the methodological use of prepositions in the works of the famous prose-writer T. Kaypbergenov. Basically, the borrowings the main characters and the personages of the work use skillfully in the language are proved with the examples. The function of auxiliary words assumed to be in the literary language is analyzed.